2015
DOI: 10.1097/md.0000000000001294
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of and Risk Factors for Neck Muscle Atrophy and Weakness in Nasopharyngeal Carcinoma Treated With Intensity-Modulated Radiotherapy

Abstract: The aim of this study was to investigate the evolution of sternocleidomastoid muscle (SCM) atrophy in nasopharyngeal carcinoma (NPC) patients following intensity-modulated radiotherapy (IMRT), and the relationship between SCM atrophy and neck weakness.Data were retrospectively analyzed from 223 biopsy-proven NPC patients with no distant metastasis who underwent IMRT with or without chemotherapy. The volume of SCM was measured on pretreatment magnetic resonance imaging (MRI), and MRIs were conducted 1, 2, and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Grade 2–3 SCM atrophy (SCM atrophy ratio >40%) was chosen as the study endpoint, as the risk of developing neck muscle weakness appears to increase when the degree of neck muscle atrophy is higher. Our previous and current research showed significant associations between the grade of SCM atrophy and the grade of neck weakness 21 . The current study found that 9.1% of SCMs suffered moderate or severe SCM atrophy, and 22.46% of patients had grade 2–3 neck weakness, 3-years post-IMRT.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Grade 2–3 SCM atrophy (SCM atrophy ratio >40%) was chosen as the study endpoint, as the risk of developing neck muscle weakness appears to increase when the degree of neck muscle atrophy is higher. Our previous and current research showed significant associations between the grade of SCM atrophy and the grade of neck weakness 21 . The current study found that 9.1% of SCMs suffered moderate or severe SCM atrophy, and 22.46% of patients had grade 2–3 neck weakness, 3-years post-IMRT.…”
Section: Discussionsupporting
confidence: 45%
“…We explored the risk factors (age, gender, T stage, N stage, chemotherapy, the length of time after IMRT and weight change ratio) for IMRT-induced SCM atrophy in previous research. Only the N stage and the length of time after IMRT were found to be associated with IMRT-induced SCM atrophy 21 . Therefore, in the present study patients were examined 3 years after the completion of IMRT in order to exclude the effect of time on the occurrence of this late complication.…”
Section: Discussionmentioning
confidence: 94%
“…Treatment strategies were designed using standard protocols depending on clinical TNM stage and the general patient condition. In the relevant study period, institutional guidelines recommended concurrent chemoradiotherapy ± neoadjuvant/adjuvant chemotherapy for stage II to IVB as described previously . Every patient was treated with IMRT at one fraction/day, 5 days per week.…”
Section: Methodsmentioning
confidence: 99%
“…Every patient was treated with IMRT at one fraction/day, 5 days per week. IMRT was performed as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…The dosimetric parameters were obtained from dose volume histograms (DVHs) of the SCM. We re-delineated bilateral SCMs according to our previously proposed methods [ 16 ] to generate the bilateral neck DVHs for each patient using the CERR DICOM-RT toolbox (version 3.0 beta 3; School of Medicine, Washington University, St. Louis, USA). The following dosimetric parameters were collected: mean dose (Dmean), maximum dose (Dmax), minimum dose (Dmin), percentage of the SCM volume that received more than X Gy (VX), the dose received by X% of the SCM volume (DX); values of X were 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75 and 80.…”
Section: Methodsmentioning
confidence: 99%